Multi-criteria decision making for smartphone brand selection using Neutrosophic Soft Set - Firdawati Mohamed,; Nur Ain Sabrina Adi Sabri,; Zakira Fadhlina Za’abar,; Norarida Abd Rhani,; Siti Nurul Fitriah Mohamad, (Penerbit Universiti Kebangsaan Malaysia, 2023)
This study explores the use of Neutrosophic Soft Set (NSS) in selecting the best smartphone brand for consumers, as the market is flooded with numerous brands and criteria, making it challenging for consumers to choose a smartphone that aligns with their preferences and interests. NSS is a mathematical tool that is effective in resolving decision-making problems involving uncertainty and inconsistent data. The study's objective is to demonstrate that NSS successfully handles complex decision-making problems involving uncertainty and inconsistent data. The study's results indicate that NSS can effectively manage high levels of uncertainty in smartphone selection, making it a valuable tool for consumers faced with such decisions. The result obtained by NSS for the chosen criteria and alternative is then used in comparative analysis to assess the accuracy of the method.